Sentiment Analysis of Multilingual Tweets on Cash Waqf - Ririn Riani; Aam; Ihsanul Ikhwan (SMART Insight, 2022)
The practice of waqf is usually focused on a building or piece of land. Many donors end up not being able to afford the assets to participate in the Waqf. Cash waqf allows people of all backgrounds to engage in long-term charitable work. This study aims to analyze the sentiment generated from the social media ‘Twitter’ application regarding cash waqf. The technique employed is sentiment analysis of secondary data consisting of 330 tweets. The results showed that positive sentiment was the highest result with a percentage of 53%, followed by neutral sentiment at 32.1%, and negative sentiment at 14.8%. The good (positive) sentiment is the opinion of Twitter users who tweet about cash waqf topics by being positive and tend to be optimistic in responding to the existence of cash waqf and supporting the development of cash waqf. While the negative sentiment is the opinion of Twitter users who tend to express criticism in reviewing developments related to cash waqf. According to the findings, the majority of individuals are more pleased about the existence of cash waqf. As a result, increasing the number of scientific literature publications in indexed journals of cash waqf is necessary to maintain this favorable view.